Negotiating Identity: The Impact of Cultural Displacement, Memory and Adaptation on Children in Haiti is My Home - Haminudin, Aileen Rihana; Ang, Angelo Gallardo; Sarijowan, Meicy Sabbathany; Sandova, Jeshelyn Enjelina (Jurnal Pendidikan Makarios, 2024)
This research analyzes "Haiti Is My Home" through the framework of Stuart Hall's Cultural Identity Theory (1990), investigating the emotional and psychological impacts of displacement on children, the influence of memory and nostalgia in identity formation, and the varied approaches to adaptation within a novel environment. The narrative centers on Marie, a young girl who is uprooted from Haiti to Boston following a catastrophic earthquake, as she endeavors to acclimate to her new surroundings while her cousin Johanne fully embraces their altered circumstances. The findings indicate: 1) The examination illustrates that displacement profoundly undermines Marie's sense of self. Her emotional and psychological distress is manifest in her struggle to reconcile her past in Haiti with her current reality in Boston, intensing in feelings of alienation and resistance to assimilation. Conversely, Johanne embodies the constructive potential of adaptation, exhibiting resilience and enthusiasm regarding their newfound situation. 2) Memory and nostalgia are crucial in the formation of Marie's identity, as her recollections of Haiti offer comfort, yet simultaneously worsen her alienation from Boston. Sensory stimuli, such as the aroma of familiar cuisine, tether Marie to her past, complicating her adjustment to her new environment. 3) The contrasting behaviors of Marie and Johanne underscore the varied ways in which individuals cope with displacement, illustrating that adaptation is shaped by both individual experiences and emotional connections to prior contexts. This suggests that cultural identity is constructed and shaped and continually redefined, especially in the context of displacement and migration. The narrative's exploration of the issue of cultural dislocation highlights that identity is not static but is continuously reshaped in response to emerging realities.